Analisis Undang-Undang Perlindungan Data Pribadi Dalam Perspektif Nilai Pancasila: Personal Data Protection Law: An Analysis from the Perspective of Pancasila Values - Muhd. Wildan Riyansyah; Nur Hadiyati; M. Naufal Anshari; Anisa Tia Mulyani; Evelyn Fenecia (Badan Pembinaan Ideologi Pancasila, 2026)
The rapid development of globalization in information and communication technology has led companies to collect and analyze user data. Personal data protection is a fundamental right that ensures data is used appropriately. This study aims to theoretically examine whether Law No. 27 of 2022 reflects the values of Pancasila as outlined in BPIP Regulation No. 4 of 2020. The research uses a juridical-normative method with legislative and conceptual approaches. Law No. 27 of 2022 explicitly mentions in its preamble and Article 4 paragraph (3) that personal data includes religious elements, reflecting the first principle of Pancasila—Belief in One Supreme God—through trust and responsibility in data confidentiality. The second principle—Just and Civilized Humanity—is reflected in Articles 25 and 26. The third principle—Indonesian Unity—is relevant because data privacy breaches can threaten national integrity. The law’s formation process embodies the fourth principle—Democracy—by accommodating public participation. Article 16 paragraph (2) guarantees equal protection of personal data, aligning with the fifth principle—Social Justice. Thus, Law No. 27 of 2022 incorporates all five principles of Pancasila as the foundation of national law.